2021
DOI: 10.21203/rs.3.rs-576971/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA-KCNQ1OT1: A Potential Target in Exosomes Derived From ADSCs for The Treatment of Osteoporosis

Abstract: Background Osteoporosis is a worldwide medical and socioeconomic threat characterized by systemic impairment to bone strength and microstructure. Exosomes derived from adipose-derived stem cells (ADSCs-Exos) have been confirmed to play effective roles in the repair of various tissues and organs. This study aimed to investigate the role of ADSCs-Exos and a noval long none coding RNAKCNQ1OT1 (lnc-KCNQ1OT1) played in osteoporosis as well as the underlying mechanism. Methods MC3T3-E1 cells were treated with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…AMSC-derived exosomes. Previous studies showed that AMSC-derived exosomes could inhibit the activation of NLRP3 inflammasome in osteoclasts and reduce the apoptosis of osteoblasts to relieve OP ( Ren et al, 2019 ; Wang S. et al, 2021 ; Zhang L. et al, 2021 ). Furthermore, Yang S. et al (2020) demonstrated that miR-130a-3p played a vital role in determining the osteogenic differentiation of AMSCs-derived exosomes.…”
Section: Exosomes and Bone Diseasesmentioning
confidence: 99%
“…AMSC-derived exosomes. Previous studies showed that AMSC-derived exosomes could inhibit the activation of NLRP3 inflammasome in osteoclasts and reduce the apoptosis of osteoblasts to relieve OP ( Ren et al, 2019 ; Wang S. et al, 2021 ; Zhang L. et al, 2021 ). Furthermore, Yang S. et al (2020) demonstrated that miR-130a-3p played a vital role in determining the osteogenic differentiation of AMSCs-derived exosomes.…”
Section: Exosomes and Bone Diseasesmentioning
confidence: 99%